Underdevelopment : a strategy for reform - Sylos Labini, Paolo (Federico Caffè lectures., 2001)
Developing countries represent the greatest challenge of our time. Sylos Labini suggests a strategy of institutional reform. For Africa, he recommends organizational reforms consisting of two European centers to tackle illiteracy, and one to promote rural and industrial districts. Finally, he proposes an international research program to explore problems of underdevelopment.